Dynamics and Characteristics of Compound Heatwaves over Asia - Ha, KyungJa; Seo, YeWon (MAUSAM, 2023)
The increasing frequency of heat waves in East Asia (EA) affects agriculture, water management, and people’s livelihoods. In recent years, record-breaking heatwaves have occurred corresponding to extreme drought and are increasing in frequency. The two leading modes of heatwavesoverEA are closely related to dry conditions, but their temporal developments are somewhat different. The first major mode of heatwaves appears over northern EA, starting in early summer and lasting throughout the summer. The second mode of heatwaves occurs over central China and Korea and is closely related to negative precipitation anomalies during late summer and startsin July or August.This study investigated the quantitative feedback attribution of heatwave-related surface temperature anomalies using the coupled air-surface climate feedback-response analysis (CFRAM). The warming anomalies related tothe first mode of heatwaves are usually controlled by cloud, latent heat, and surface dynamics processes. It can be explained by reducing heat release from the surface to the atmosphere due to the lack of soil moisture under severe dry conditions.While surface warming related to the second mode of heatwaves is contributed by cloud feedback and atmospheric dynamic process. Reduction in cloud area associated with anticycloniccirculation anomalies induces increased insolation and it affects surface warming. However, the effect of humidity on high-temperature events has not yet been fully explored. Thus, this study identifiedcompound heatwaves that are described simultaneously with relative humidity conditions and suggested the future projections of two types of heatwaves over EA using phase six of the Coupled Model Intercomparison Project (CMIP6) model simulation. CMIP6 models projected intensification of dry heatwaves and increased moist heatwave days in response to projected increases in greenhouse gas concentrations.